Family Structure and Early Marriage on Women in Indramayu Regency - Muharry, Andy; Hakimi, Mohammad; Wahyuni, Budi (KEMAS: Jurnal Kesehatan Masyarakat, 2018)
Early marriage in Indramayu Regency in the past two years had increased to three times. The purpose of this research was to identify the age of marriage and the factors which caused early marriage by looking at the variables of family structure, education and economic status of the household. This research used matched case control study design. The data were collected using questionnaires and interview guidelines. The samples were taken using simple random sampling technique. The subject consisted of 94 people. The data were analysed using McNemar test and conditional logistic regression. The variables which had significant relationship with early marriage were father’s education, education of the respondents, and economic status of the household. Meanwhile, family structure and mother’s education had no significant relationship with early marriage. It can be concluded that women with low father’s education and came from poor families had greater chance of getting married early.